1992
DOI: 10.1083/jcb.118.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Different extracellular domains of the neural cell adhesion molecule (N-CAM) are involved in different functions.

Abstract: Abstract. The neural cell adhesion molecule (N-CAM) engages in diverse functional roles in neural cell interactions. Its extracellular part consists of five Ig-like domains and two fibronectin type III homologous (type III) repeats. To investigate the functional properties of the different structural domains of the molecule in cell interactions and signal transduction to the cell interior, we have synthesized, in a bacterial expression system, the individual domains and tandem sets of individual domains as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
78
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 96 publications
(88 reference statements)
6
78
1
Order By: Relevance
“…Our data are also in accord with a variety of results (2,18,19,21) that suggest that Ig III has a special role in N-CAM binding and indicate that this effect is due to the ability of Ig III to interact with itself. Our results and those from cellular transfection studies (17, 18, 21, from a recent report (23) There is no evidence that the carbohydrates play a direct role in N-CAM binding, although the ability of polysialic acid to modulate binding (15) is prominent. It should be pointed out that none of our recombinant domains is glycosylated whereas Ig III, IV, and V are probably glycosylated in the intact molecule in vivo (2,9).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Our data are also in accord with a variety of results (2,18,19,21) that suggest that Ig III has a special role in N-CAM binding and indicate that this effect is due to the ability of Ig III to interact with itself. Our results and those from cellular transfection studies (17, 18, 21, from a recent report (23) There is no evidence that the carbohydrates play a direct role in N-CAM binding, although the ability of polysialic acid to modulate binding (15) is prominent. It should be pointed out that none of our recombinant domains is glycosylated whereas Ig III, IV, and V are probably glycosylated in the intact molecule in vivo (2,9).…”
Section: Resultssupporting
confidence: 65%
“…This study, however, did not reveal which of the domains specifically interact with the others. Another transfection study using only N-CAM constructs indicated that mutations in Ig III had a significant effect on N-CAM binding and showed that peptides corresponding to a short region of Ig III could inhibit adhesion (18,21,22 (23).…”
mentioning
confidence: 99%
“…Thus, the neurite-outgrowth response to NCAM can be abolished by pertussis toxin, an inhibitor of G proteins, and this response is strongly reduced by Ca2+ channel blockers (24). Triggering of cell-surface NCAM by NCAM antibodies (25) as well as by various NCAM fragments (26) can modulate intracellular levels of inositol phosphates, Ca2+, and pH. The fact that expression of both NCAM isoforms mediated cell aggregation, whereas only NCAM-B expression decreased secreted metalloproteinase activity, indicates that the presumed signal for this down-regulation may be transduced by NCAM-B itself.…”
Section: Resultsmentioning
confidence: 99%
“…Most members of the neural adhesion subfamily have been shown to possess both such adhesive and axon outgrowth activities in vitro (5,11). In various molecules studied, these activities have been mapped to both the IgC2 and FNIII or independently on either one of the two domains (17,(22)(23)(24)(25).…”
mentioning
confidence: 99%